An LSH Based Time Subsequence Matching Algorithm - Genping Liu; Yefang Chen; Chengtou Du; Jiangbo Qian (Dianxin kexue)
An algorithm called LSHSM，which uses locality sensitive hashing（LSH）to process time subsequence matching，was proposed.Different to the FRM and DualMatch algorithms，the LSHSM does not require feature transformation such as DFT and DWT.It just directly regards the sequence as a high-dimensional object to find similar subsequences.Comparing to a linear algorithm on three real datasets，the LSHSM algorithm demonstrates the effectiveness and efficiency.